IMPACT OF COVID ON INDIAN ECONOMY - SHARMA, POONAM (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
In the middle of a global Covid-19 pandemic, which is inflicting two kinds of shocks on countries: a health shock and an economic shock. Given the nature of the disease which is highly contagious, the ways to contain the spread include policy actions such as imposition of social distancing, self-isolation at home, closure of institutions, and public facilities, restrictions on mobility and even lock-down of an entire country. These actions can potentially lead to dire consequences for economies around the world. On April 9, the chief of International Monetary Fund, Kristalina Georgieva said that the year 2020 could see the worst global economic fallout since the Great Depression in the 1930s, with over 170 countries likely to experience negative per capita GDP growth due to the raging corona virus pandemic. The Indian economy in the pre Covid-19 period and assess the potential impact of the shock on various segments of the economy. We discuss the policies that have been announced so far to ameliorate the economic shock and finally end with some policy recommendations.